PRAGMATIC INTENSIFIERS OF NEWSPAPER ANALYTICAL TEXT (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Newspaper pragmatics refers to the field of research that occupies an essential place in the linguistic science devoted to modern newspaper speech. The pragmatic aspect of studying a newspaper text is very relevant because attention to this problem allows you to deeply understand the linguistic mechanism of influencing a mass audience with the help of mass media designed not only to cover current events, but also to convince, predict and influence.